2020
DOI: 10.1002/jmv.25957
|View full text |Cite
|
Sign up to set email alerts
|

Elevations of serum cancer biomarkers correlate with severity of COVID‐19

Abstract: In this retrospective study, we evaluated the levels of a series of serum biomarkers in coronavirus disease 2019 (COVID-19) patients (mild: 131; severe: 98; critical: 23). We found that there were significant increases in levels of human epididymis protein 4 (HE4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
95
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(114 citation statements)
references
References 21 publications
(51 reference statements)
13
95
2
Order By: Relevance
“…However, the role of CEA levels in clinical outcomes or CT involvements of COVID-19 patients was still unknown. This study validated the previous result that CEA levels were related to severity of COVID-19 reported by different research groups (Union Hospital of Tongji Medical College, Wuhan) ( 19 ). Furthermore, our study concentrated on different CEA levels in COVID-19 patients with different clinical outcomes (survivors or non-survivors) and potential correlations with CT involvement scores.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the role of CEA levels in clinical outcomes or CT involvements of COVID-19 patients was still unknown. This study validated the previous result that CEA levels were related to severity of COVID-19 reported by different research groups (Union Hospital of Tongji Medical College, Wuhan) ( 19 ). Furthermore, our study concentrated on different CEA levels in COVID-19 patients with different clinical outcomes (survivors or non-survivors) and potential correlations with CT involvement scores.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, increasing levels of serum CEA were associated with more CT involvement scores in discharged COVID-19 patients. Till now, only one study reported the elevated serum CEA levels in COVID-19 patients ( 19 ). In that retrospective study, the authors found significant increases of CEA levels compared with health controls and a potential association between CEA and CRP levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiuqu W. et al showed elevations of serum cancer biomarkers in COVID-19 patients: squamous cell carcinoma antigens (SCC) and CA19.9 only in critical cases, carcinoembryonic antigen (CEA), carbohydrate antigens (CA-125, CA-153), cytocheretin-19 fragment (CYFRA21-1), HE4 in mild, severe and critical cases and concluded that elevations of these biomarkers is correlated with the pathological progressions of COVID-19 [40].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the elevation of several inflammatory/immunological biomarkers, they also noticed a positive association between the levels of cancer biomarkers with disease severity. 132 In a study, the proteomic and metabolic profiling of patient plasma, including samples from patients before they progressed to severe disease, was carried out using TMT. 133 To predict if a patient will develop severe disease, the data were fed into a machine learning model that was then trained.…”
Section: Coronavirusesmentioning
confidence: 99%